2013
DOI: 10.1186/1475-2867-13-6
|View full text |Cite
|
Sign up to set email alerts
|

Combining the negative lymph nodes count with the ratio of positive and removed lymph nodes can better predict the postoperative survival in cervical cancer patients

Abstract: BackgroundTo evaluate the impacts of the negative lymph nodes (NLNs) count on the prognostic prediction of the ratio of positive and removed lymph nodes (RPL) in cervical cancer patients after radical hysterectomy and pelvic lymphadenectomy (RHPL).MethodsThe positive and negative lymph node counts were calculated for 609 postoperative cervical cancer patients. The 5-year survival rate (5-YSR) was examined according to clinicopathologic variables. Cox regression was used to identify independent prognostic facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 26 publications
0
36
2
Order By: Relevance
“…[1315] Polterauer et al reported on a series of 88 consecutive node-positive patients and found that patients with a LNR>10% had a worse disease-free (HR=2.2, 95% CI 1.1–4.7, p=0.01) and overall survival (HR=2.2, 95% CI 1.0–4.8, p=0.05) compared to those patients with a LNR ≤ 10%. However, this series included all node-positive patients with locally advanced cervical cancer from stage IB1 to IVA treated with primary chemoradiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1315] Polterauer et al reported on a series of 88 consecutive node-positive patients and found that patients with a LNR>10% had a worse disease-free (HR=2.2, 95% CI 1.1–4.7, p=0.01) and overall survival (HR=2.2, 95% CI 1.0–4.8, p=0.05) compared to those patients with a LNR ≤ 10%. However, this series included all node-positive patients with locally advanced cervical cancer from stage IB1 to IVA treated with primary chemoradiation.…”
Section: Discussionmentioning
confidence: 99%
“…[1112] A significant correlation between LNR and survival has also been seen in cervical cancer in single-institution retrospective studies, however, across all stage distributions and in patients receiving neoadjuvant chemotherapy prior to surgery. [1315]…”
Section: Introductionmentioning
confidence: 99%
“…It's necessary to bring NLN count into the system of prognosis prediction in breast cancer. Many researchers have suggested that NLN count is closely related to the prognosis in gastric cancer (11), colon cancer (12), esophageal cancer (13), and cervical cancer (14). However, few data has been published to elucidate the importance of NLN count in breast cancer prognosis.…”
Section: Original Articlementioning
confidence: 99%
“…While the node-positive patients with RC are heterogeneous and the prognosis of these patients cannot be stratified by the node-stage only [3, 4]. Therefore, the concept of negative lymph node (NLN) counts has attracted attention recently as a prognostic indicator in various cancers, including breast [5], cervical [6], and esophagus [7]. It has been reported that the number of NLNs was an independent prognostic factor for patients with colon cancer [8].…”
Section: Introductionmentioning
confidence: 99%